Endoscopic ultrasound-guided cholecystostomy for resection of gallbladder polyps with lumen-apposing metal stent. Issue 43 (23rd October 2020) - Shen, Yonghua; Cao, Jun; Zhou, Xiaoliang; Zhang, Song; Li, Juan; Xu, Guifang; Zou, Xiaoping; Lu, Ying; Yao, Yuling; Wang, Lei
Abstract : Abstract: Laparoscopic cholecystectomy is the routine method to treat gallbladder polyps. Nowadays, endoscopic ultrasound (EUS)-guided cholecystostomy as a bridge for per-oral transmural endoscopic resection of gallbladder polyps is introduced because preservation of gallbladder is increasingly getting attention. The aim of our study was to evaluate the approach in the treatment of patients with gallbladder polyps and symptomatic gallstones. EUS-guided cholecystostomy with the placement of a lumen-apposing metal stent (LAMS) was performed for those patients with accompanying gallbladder polyps and symptomatic gallstones. Several days after the cholecystostomy with LAMS, a gastroscope was introduced into the gallbladder to remove gallbladder polyps. All patients were successfully performed with the procedures of EUS-guided cholecystoduodenostomy (n = 3) or cholecystogastrostomy (n = 1) and endoscopic resection of gallbladder polyps. One patient experienced severe peritonitis. During the follow-up at 3 months, 1 patient was performed with laparoscopic cholecystectomy because ultrasonography examination showed the reappeared gallstones. No stone recurrence was found in other patients. During the follow-up of 3 to 15 months, no polyp recurrence was found in all the patients. The approach is novel for performing EUS-guided gallbladder fistulization, which can subsequently allow procedures of per-oral transmural endoscopic resection of gallbladder polyps to avoid cholecystectomy in the patients with gallbladder polyps and gallstones. However, further studies are needed before clinical recommendation because of the complications and stone recurrence.